The relationship between multisite peripheral joint pain and physical activity levels in older adults: A cross‐sectional survey. (28th September 2021) - Smith, Robert D.; McHugh, Gretl A.; Quicke, Jonathan G.; Finney, Andrew; Lewis, Martyn; Dziedzic, Krysia S.; Healey, Emma L.
Abstract: Introduction: Research on levels of physical activity (PA) in those with peripheral joint pain have only focused on single sites, in the knee or hips. This study investigated the levels of PA in adults with single‐site and multisite peripheral joint pain compared to adults with no joint pain. Methods: Analysis of a cross‐sectional population survey mailed to adults aged ≥45 years ( n = 28, 443) was conducted. Respondents reported any peripheral joint pain in the last 12 months in either the hands, hips, knees or feet; PA levels were self‐reported using the short telephone activity rating scale. The association between PA levels, peripheral joint pain and outcomes of health status (physical and mental component scores, using SF‐12) pain intensity (10‐point scale) and health‐related quality of life (HRQoL) (EQ‐5D) were investigated using analysis of variance and ordinal regressions. Results: Compared to those with no joint pain, all pain groups reported lower levels of PA: joint pain in one site (odds ratio = 0.91, 95% CI: 0.83–0.99); two sites (0.74, 0.67–0.81), three sites (0.65, 0.59–0.72) and four sites (0.47, 0.42–0.53). Across all joint pain groups, levels of PA were associated with pain intensity, physical health status, mental health status and HRQoL. Discussion: Adults with more sites of peripheral joint pain were more likely to report lower levels of PA. Those with more sites of pain and lower levels of PA reported poorer outcomes. Health care providers should be aware that those with multisite joint pain are most likely to have low levels of PA.